Solving inverse scattering problems in biological samples by quantitative phase imaging. Issue 1 (16th December 2015) - Kim, Taewoo; Zhou, Renjie; Goddard, Lynford L.; Popescu, Gabriel
Abstract : Quantitative phase imaging (QPI) precisely recovers the wavefront of an electromagnetic field scattered by a transparent, weakly scattering object. In the past decade, 3D optical tomographic reconstruction methods based on QPI techniques to solve inverse scattering problems have made significant progress. This review highlights a number of advances and developments in QPI including Fourier transform light scattering (FTLS), optical diffraction tomography (ODT), and white‐light diffraction tomography (WDT). Abstract: Quantitative phase imaging (QPI), a method that precisely recovers the wavefront of an electromagnetic field scattered by a transparent, weakly scattering object, is a rapidly growing field of study. By solving the inverse scattering problem, the structure of the scattering object can be reconstructed from QPI data. In the past decade, 3D optical tomographic reconstruction methods based on QPI techniques to solve inverse scattering problems have made significant progress. In this review, we highlight a number of these advances and developments. In particular, we cover in depth Fourier transform light scattering (FTLS), optical diffraction tomography (ODT), and white‐light diffraction tomography (WDT).